2014
DOI: 10.4236/wja.2014.41003
|View full text |Cite
|
Sign up to set email alerts
|

Perceived Social Support among HIV Positive and HIV Negative People in Ibadan, Nigeria

Abstract: Background: People living with HIV and AIDS (PLWHA) are assumed to have poor social support. This study compared the satisfaction with perceived social support of people living with HIV and AIDS with HIV negative patients. Method: 150 HIV positive patients were age and sex matched with 150 HIV negative patients in a cross sectional comparative study. Information on socio-demography and social support was assessed with questionnaire including multidimensional scale of perceived social support (MSPSS). Chi squar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 20 publications
0
11
0
Order By: Relevance
“…Items are rated on a 5-point Likert-type scale, ranging from strongly disagree (1) to strongly agree (5). Based on previous research (e.g., Folasire et al, 2014), a significant other was explained as a special person that the respondent feels closer to besides family and friends and with whom one can discuss personal issues (e.g., church leaders/members, teachers, and colleagues). The three support sources as contained in MSPSS have been identified to be among the major sources of support among PLWHA in Africa (see Lypen et al, 2015).…”
Section: Methodsmentioning
confidence: 99%
“…Items are rated on a 5-point Likert-type scale, ranging from strongly disagree (1) to strongly agree (5). Based on previous research (e.g., Folasire et al, 2014), a significant other was explained as a special person that the respondent feels closer to besides family and friends and with whom one can discuss personal issues (e.g., church leaders/members, teachers, and colleagues). The three support sources as contained in MSPSS have been identified to be among the major sources of support among PLWHA in Africa (see Lypen et al, 2015).…”
Section: Methodsmentioning
confidence: 99%
“…In this study, low level of perceived social support was found to be significantly associated with certain factors which included female gender, age group ≥ 45 years, shorter known duration of HIV diagnosis, lower educational status, lower monthly income, unemployed status and no history of affiliation with a support group. A study in the western part of Nigeria also identified lack of employment as a significant factor in low level of perceived social support [22]. This relationship between perceived social support and some of the listed factors can be attributed to the fact that in many instances, a lower level of education is more likely to result in a lower income or even unemployment and the ensuing need to rely on others for material and ultimately social support.…”
Section: Discussionmentioning
confidence: 99%
“…The results of the study of Ebachi and Behroan showed that the severe stigma affects the health of the individual and the community, and with the acceptance of these patients in society, the burden of mental illness can be reduced and life satisfaction increases [31]. A study conducted in 2013 in Nigeria showed that people who are supported by the community and the family and have a family background and job have the best status, and those who are rejected from the family are in the worst situation [13]. In relation to psychiatric support there are so many different ways in which one of the best practices is the self-care approach, so that psychological components in people are strengthened so much that sick people themselves take care of their health.…”
Section: Discussionmentioning
confidence: 99%
“…To control this hygiene, social and cultural challenge, it seems that we should seek to change the behavior of the affected individuals and those with high-risk behaviors in the community [12]. Chronic disease especially HIV has a severe negative impact on the quality of life, mental health and the economic situation of the community [13][14][15] and families with AIDS [16,17] and neglecting the lives of AIDS patients, lack of proper social status, acquiring a social stigma [18], etc., makes these patients be involved in irresponsible behaviors that lead to the spread of the virus and infection of large numbers of people in the community [19]. Considering the above-mentioned issues, in order to improve the quality of life, we must seek to reduce the social, health, cultural and economic problems of AIDS patients, and this cannot be achieved except by the efforts of all people in the community, especially the healthcare team that through appropriate treatment and gaining the confidence of these patients and organizing classes and study sessions, understands their problems so that patients feel that the community values them and they are treated like other patients, they can learn and can identify their problems and get guidance.…”
Section: Introductionmentioning
confidence: 99%